2018
DOI: 10.1016/j.jeurceramsoc.2017.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up aqueous processing of A-site deficient strontium titanate for SOFC anode supports

Abstract: All ceramic anode supported half cells of technically relevant scale were fabricated in this study, using a novel strontium titanate anode material. The use of this material would be highly advantageous in solid oxide fuel cells due to its redox tolerance and resistance to coking and sulphur poisoning. Successful fabrication was possible through aqueous tape casting of both anode support and electrolyte layers and subsequent lamination. Screen printing of electrolyte layers onto green anode tapes was also atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…[187] Anode supported half cells were successfully manufactured by aqueous tape casting and infiltration, where LSCT A− was the supporting scaffold for infiltration with different types of ceria impregnated. [187] Anode supported half cells were successfully manufactured by aqueous tape casting and infiltration, where LSCT A− was the supporting scaffold for infiltration with different types of ceria impregnated.…”
Section: Scaleup and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…[187] Anode supported half cells were successfully manufactured by aqueous tape casting and infiltration, where LSCT A− was the supporting scaffold for infiltration with different types of ceria impregnated. [187] Anode supported half cells were successfully manufactured by aqueous tape casting and infiltration, where LSCT A− was the supporting scaffold for infiltration with different types of ceria impregnated.…”
Section: Scaleup and Outlookmentioning
confidence: 99%
“…An attempt to transfer developed ceramic formulations and methods in the lab to an industrial relevant level with novel ceramic materials has been reported recently on aqueous tape casting and subsequent infiltration . Anode supported half cells were successfully manufactured by aqueous tape casting and infiltration, where LSCT A− was the supporting scaffold for infiltration with different types of ceria impregnated.…”
Section: Scaleup and Outlookmentioning
confidence: 99%
“…A typical SOFC fuel electrode material that displays outstanding catalytic performance in hydrogen is Ni-cermet. However, this electrode is not very stable and attractive in hydrocarbon fuels because of its quick carbon deposition at operating temperatures and the necessity for a high water concentration in the fuel stream to suppress the carbon deposition (which leads to decrease of the SOFC power characteristics). Additionally, Ni-based fuel electrodes are very sensitive against impurities like H 2 S in natural gas and HCl, as well as KCl in syngas, ,, and tend to re-oxidize at higher cell loads. A large number of studies has been devoted to diminishing these drawbacks by exploring new materials to replace the Ni-cermet fuel electrode. ,, One attractive branch of novel electrode materials is perovskite-type complex oxides (ABO 3 ) with mixed ionic–electronic conductivity (MIEC).…”
Section: Introductionmentioning
confidence: 99%
“…La 0.20 Sr 0.25 Ca 0.45 TiO 3 (LSCT) was synthesized using this method, and its scanning electron microscope (SEM) micrograph is shown in Figure where black areas are pores and the regions that are darker having grey colour can be seen as secondary phase, ie, rutile. The particle size could be controlled by changing calcination temperatures . (2) Ultrasonic spray pyrolysis: MWs are used and adjusting the frequency one can control the size of drops .…”
Section: Methods For Synthesis Of Sofc Anodesmentioning
confidence: 99%
“…The particle size could be controlled by changing calcination temperatures. 149 (2) Ultrasonic spray pyrolysis: MWs are used and adjusting the frequency one can control the size of drops. 150 (3) Flame spray pyrolysis is accomplished in three steps: firstly, aerosol production takes place; then, combustion is done, and finally, powder is collected.…”
Section: Pyrolysis Methodsmentioning
confidence: 99%